Corruption and Military Spending. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
Anecdotal evidence relates corruption with high levels of military spending. This paper tests empirically whether such a relationship exists. The empirical analysis is based on data from four different sources for up to 120 countries in the period 1985-98. The association between military spending and corruption is ascertained by using panel regression techniques. The results suggest that corruption is indeed associated with higher military spending as a share of both GDP and total government spending, as well as with arms procurement in relation to GDP and total government spending. This evidence indicates that defense spending can be considered for constructing governance indicators.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Russian Federation